2019
DOI: 10.1242/jeb.196261
|View full text |Cite
|
Sign up to set email alerts
|

Responses of compass neurons in the locust brain to visual motion and leg motor activity

Abstract: The central complex, a group of midline neuropils in the insect brain, plays a key role in spatial orientation and navigation. Work in locusts, crickets, dung beetles, bees and butterflies suggests that it harbors a network of neurons which determines the orientation of the insect relative to the pattern of polarized light in the blue sky. In locusts, these 'compass cells' also respond to simulated approaching objects. Here, we investigated in the locust Schistocerca gregaria whether compass cells change their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 64 publications
0
19
1
Order By: Relevance
“…Interestingly, calcium imaging data from Drosophila showed that visual stimuli elicit activity in the fan‐shaped body (equivalent to CBU) only during flight, but not when the animal is at rest (Weir & Dickinson, ) suggesting that visual input to the CBU is gated by motor activity. Although motor activity related input to the CX is, likewise, important in the locust (Rosner, Pegel, & Homberg, ), pontine as well as tangential neurons of the CBU in restrained animals were strongly sensitive to motion stimuli (looming disc), partly in an azimuth‐dependent way (Rosner & Homberg, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, calcium imaging data from Drosophila showed that visual stimuli elicit activity in the fan‐shaped body (equivalent to CBU) only during flight, but not when the animal is at rest (Weir & Dickinson, ) suggesting that visual input to the CBU is gated by motor activity. Although motor activity related input to the CX is, likewise, important in the locust (Rosner, Pegel, & Homberg, ), pontine as well as tangential neurons of the CBU in restrained animals were strongly sensitive to motion stimuli (looming disc), partly in an azimuth‐dependent way (Rosner & Homberg, ).…”
Section: Discussionmentioning
confidence: 99%
“…The posterior slope is the major input site of TB4–TB7 neurons to the PB, but certain neurons to the CBL (TL5, Figure f), the CBU (TU VES 3, Figure e; TU PS1 3, Figure c) and the noduli (TN, Figure ) also ramify in the posterior slope, which thus provides input to all CX subunits. Based on the strong innervation by intersegmental interneurons, these inputs might serve to monitor the behavioral state of the animal, which strongly influences neural excitation in the CX at all levels (Homberg, ; Rosner et al, ), likely to prioritize navigation relevant information input during walking and flight (Pfeiffer & Homberg, ).…”
Section: Discussionmentioning
confidence: 99%
“…This extensive colocalization of neuroactive substances further increases the ways by which modulation of the neural circuitries in the central complex can occur. A number of functional studies have already pointed out that neural activity and signaling in the central complex is highly dependent on the behavioral state of the animal (Heinze & Homberg, 2009;Rosner, Pegel, & Homberg, 2019;Weir, Schnell, & Dickinson, 2014) and, in addition, is involved in circadian control of locomotor and sleep-wake cycles (Donlea et al, 2018;Liang et al, 2019;Liu, Liu, Tabuchi, & Wu, 2016).…”
Section: Colocalization Of Neuroactive Substancesmentioning
confidence: 99%
“…As the butterflies used the dark stripe for flight control, the neuronal basis for it lies likely in the motion vision center, the lobula plate of the optic lobe (Meier and Borst, 2019;Ullrich et al, 2015). Although some optic-flow information is integrated into the central complex in locusts and bees (Rosner et al, 2019;Stone et al, 2017), the relevant information for flight control is directly transferred to the thoracic ganglia via descending pathways (Suver et al, 2016). In fruit flies, attraction does not require the activity of the central complex (Giraldo et al, 2018).…”
Section: Neuronal Network Behind Orientationmentioning
confidence: 99%